SUBSTANTIATION OF SOCIO-ECONOMIC AND ECOLOGICAL CONSEQUENCES OF PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF EDUCATION - Maslov , Vladyslav (Socio-economic relations in the digital society, 2021)
The article comprehensively considers all aspects of preparation and implementation of public-private partnership projects in the field of education in terms of economic, financial, social, legal, technical and environmental parameters in order to identify needs and opportunities for their implementation, necessary investments (resources) and expected results. Also, it is provided conclusions on which partners can be convinced of the need to implement such public-private partnership (РРР) projects. The purpose of the article is to analyze the economic, social, environmental indicators of PPP implementation, assessment of the identified risks of PPP implementation for public and private partners. The basic concept of assessing the socio-economic and environmental factors influencing the education sector should be the concept of opportunity cost of economic analysis, which shows that because all resources of society are limited and can have different uses, their value should be measured in terms of lost opportunity to engage in the best available alternatives. activities that require the use of the same resources. The paper considers the risks of PPP projects and based on the use of methods for assessing such risks, gives recommendations for their management by PPP participants. It is proved that the implementation of PPP projects in the field of education will provide: intensive development and improvement of the quality of education and research; orientation of educational and scientific activity on coordination of needs of the state, inquiries of national economy, individual interests and preferences (applicants of higher education, scientific and scientific and pedagogical workers, businessmen, representatives of the business environment, etc.); improving the efficiency of property management of higher education institutions; attracting private investment in the development of educational institutions; strengthening the economic capacity and financial autonomy of higher education institutions; increasing the level of financial and social security of the subjects of the educational and scientific process.
Keywords: public-private partnership; risks; environmental assessment; socio-economic assessment; public-private university